Recent progress on designing electrospun nanofibers for colorimetric biosensing applications. (March 2020) - Senthamizhan, Anitha; Balusamy, Brabu; Uyar, Tamer
Abstract: Colorimetric sensors based on nanofibers fabricated by electrospinning have gained substantial attention owing to their exceptional features including diverse fibrous morphology, surface area, porous nature, flexibility, and distinctive benefits in functionalization. The electrospun nanofiber–based membranes serve as excellent platforms in colorimetric detection of various biological molecules. The main emphasis of the review is to highlight very recent progress on development of electrospun nanofibers for detection of biomolecules in terms of their response time and high selectivity with special focus to hydrogen peroxide and l -cysteine. We present descriptive examples of the biosensing illustrating the progress in designing electrospun-based nanofibers as sensing probe/support. Furthermore, summary and future outlook on the designing of electrospun nanofibers for colorimetric biosensing is discussed. Highlights: The role of electrospun nanofibers in the development of biosensor is highlighted. Recent findings in electrospun nanofiber–based colorimetric detection of H2 O2 is reviewed. Recent progress in the colorimetric detection of l -cysteine by electrospun nanofibers is provided. Discussions on future directions for developing electrospun nanofibrous sensing platform is presented.